2017
DOI: 10.1038/s41525-017-0014-7
|View full text |Cite|
|
Sign up to set email alerts
|

Genomic landscape of high-grade meningiomas

Abstract: High-grade meningiomas frequently recur and are associated with high rates of morbidity and mortality. To determine the factors that promote the development and evolution of these tumors, we analyzed the genomes of 134 high-grade meningiomas and compared this information with data from 595 previously published meningiomas. High-grade meningiomas had a higher mutation burden than low-grade meningiomas but did not harbor any significantly mutated genes aside from NF2. High-grade meningiomas also possessed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
161
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(180 citation statements)
references
References 64 publications
(115 reference statements)
15
161
2
2
Order By: Relevance
“…A major difference between our study and previous explorations of the genomic landscape of meningioma is that those studies maintained the framework of the existing WHO histopathological classification for their molecular analysis (13,(15)(16)(17)(18)(19)44). For example, one study of atypical (grade II) tumors found the majority to have NF2/chr22q loss and genomic instability along with overexpression of the E2F2 and FOXM1 transcriptional networks (13).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…A major difference between our study and previous explorations of the genomic landscape of meningioma is that those studies maintained the framework of the existing WHO histopathological classification for their molecular analysis (13,(15)(16)(17)(18)(19)44). For example, one study of atypical (grade II) tumors found the majority to have NF2/chr22q loss and genomic instability along with overexpression of the E2F2 and FOXM1 transcriptional networks (13).…”
Section: Discussionmentioning
confidence: 83%
“…Since high-grade meningiomas have more chromosomal abnormalities (13,18), we analyzed the three types of tumors for genomic instability using copy number data derived from whole-exome sequencing (WES) ( Fig. 4).…”
Section: Copy Number and Somatic Alterations In Meningiomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in LRP1B, a gene previously described as mutated in high-grade meningiomas [20], were detected in nine chordoid meningiomas, and occurred in tumors from both ED group #2 (25%) and ED group #3 (41%), without apparent predilection for location ( Figure 2A,C). LRP1B encodes a large low-density lipoprotein (LDL) receptor family member with tumor suppressor activity [21].…”
Section: Chordoid Meningioma Ed Groups Exhibit Distinct Gene Mutationmentioning
confidence: 90%
“…Many meningiomas possess a normal karyotype, with an overall low incidence of genomic alterations (i.e., somatic copy number alterations (SCNA), rearrangements, mutational burden) (10)(11)(12)(13). However, these disruptions increase in accordance with tumor grade and aggressiveness.…”
Section: Cyotgeneticsmentioning
confidence: 99%